Changes in root morphology and dry matter production in Pfaffia glomerata (Spreng.) Pedersen accessions in response to excessive zinc - K. BERNARDY; J.G. FARIAS; A.O.S. DORNELES; A.S. PEREIRA; M.R.W. SCHORR; F.R. THEWES; J.E.L. LONDERO; F.T. NICOLOSO
ABSTRACT Zinc (Zn) participates of numerous metabolic processes in plants. However, it can become toxic to plants in excessive concentrations in the soil. Pfaffia glomerata is a Brazilian medicinal species that has stood out because of its numerous chemical and functional properties, mainly by the triterpene saponins and ecdysteroids accumulated in its roots. This study aimed to evaluate the effects of zinc excess on many root morphological parameters of Pfaffia glomerata. A 4 x 3 factorial design was employed in a completely randomized scheme with 3 replicates. The treatments consisted of four concentrations of Zn (2, 100, 200, and 300 µM) and three accessions of P. glomerata (BRA, GD, and JB) grown in a hydroponic system for 7 and 14 days. Differences in root morphology and dry mass production were observed among the three accessions in response to excessive Zn. Some growth parameters of GD accession increased with the addition of Zn, ranging from 36 to 79 µM. However, the GD and JB accessions presented reduction in dry mass production, root area, length, and volume with increasing Zn levels. The BRA accession, which had the lowest growth among accessions, presented chlorotic leaves. The shoot/root dry mass ratio and root diameter increased linearly for BRA and GD accessions at 7 days. Based on the evaluated parameters, we observed the following order of Zn excess tolerance in P. glomerata accessions: GD> JB> BRA.